1979
DOI: 10.1017/s0007485300017818
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the age-composition of samples ofAnopheles darlingiRoot (Diptera: Culicidae) in Brazil

Abstract: The Polovodova ageing technique was applied to females of Anopheles darlingi Root in the northern part of Mate Grosso, Brazil, in April 1978; 1·5% of the females had oviposited at least four times and were old enough to be potential vectors of malaria. The oldest female dissected had oviposited six times. The mosquito has a resting period of at least 24 h between oviposition and the next blood-meal. There was a pronounced peak of biting activity, consisting largely of nulliparous females, at dawn and dusk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1
9

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 4 publications
2
38
1
9
Order By: Relevance
“…Considering the lack of previous data concerning An. darlingi, the duration of the gonotrophic cycle was assumed to be three days (Charlwood & Wilkes 1979) and the human blood index to be 0.5 (Rachou 1958, WHO 1960, Zimmerman et al 2006. The duration of the sporogonic cycle of P. falciparum was assumed to be 11 days, based on the temperatures recorded at the study site (WHO 1975).…”
Section: Field Mosquito Processing -mentioning
confidence: 99%
“…Considering the lack of previous data concerning An. darlingi, the duration of the gonotrophic cycle was assumed to be three days (Charlwood & Wilkes 1979) and the human blood index to be 0.5 (Rachou 1958, WHO 1960, Zimmerman et al 2006. The duration of the sporogonic cycle of P. falciparum was assumed to be 11 days, based on the temperatures recorded at the study site (WHO 1975).…”
Section: Field Mosquito Processing -mentioning
confidence: 99%
“…No substantial information concerning seasonal or geographical variation in survival have been reported, although a greater proportion of potential vectors (i.e. those that were three parous or older) were found during a limited series of dissections from Amazonas (Charlwood 1980) compared to a population from Mato Grosso (Charlwood & Wilkes 1979). Survival in these populations was age dependant and fitted a Gompertz curve (Clements & Paterson 1981).…”
mentioning
confidence: 99%
“…Early evening biting activity has been observed during population peaks for other Neotropical anophelines (Elliot 1972, Klein & Lima 1990). Charlwood and Wilkes (1979) found that the individuals of Anopheles darlingi that were biting in the crepuscular peaks observed in Mato Grosso consisted largely of nulliparous females. In considering the population peak of each species of the Triannulatus Complex, we observed that a higher number of specimens were collected at H1.…”
Section: Discussionmentioning
confidence: 97%